2017
DOI: 10.1002/evl3.21
|View full text |Cite
|
Sign up to set email alerts
|

Divergent artificial selection for female reproductive investment has a sexually concordant effect on male reproductive success

Abstract: Depending on the genetic architecture of male and female fitness, sex‐specific selection can have negative, positive, or neutral consequences for the opposite sex. Theory predicts that conflict between male and female function may drive the breakdown of intrasexual genetic correlations, allowing sexual dimorphism in sexually antagonistic traits. Reproductive traits are the epitome of this, showing highly differentiated proximate functions between the sexes. Here we use divergent artificial selection lines for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Why we found a significant difference between the 2 selection lines in males is also unexpected, particularly when one considers that maternal egg investment was selected to create the divergent lines [Pick et al, 2016a]. However, previous work in this system demonstrated correlated responses of selection for female reproductive investment on male reproductive performance, as well as changes in testes morphology in males from the divergent lines [Pick et al, 2017]. Differences in Purkinje cell size and cerebellar folding in males could thus be a direct consequence of different reproductive strategies (i.e., plastic resource allocation) and/or reflect (sex-specific) genetic correlations between reproductive performance and cerebellar morphology.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Why we found a significant difference between the 2 selection lines in males is also unexpected, particularly when one considers that maternal egg investment was selected to create the divergent lines [Pick et al, 2016a]. However, previous work in this system demonstrated correlated responses of selection for female reproductive investment on male reproductive performance, as well as changes in testes morphology in males from the divergent lines [Pick et al, 2017]. Differences in Purkinje cell size and cerebellar folding in males could thus be a direct consequence of different reproductive strategies (i.e., plastic resource allocation) and/or reflect (sex-specific) genetic correlations between reproductive performance and cerebellar morphology.…”
Section: Discussionmentioning
confidence: 49%
“…In addition to differences in egg mass, the H-line females have larger reproductive organs than L-line females [Pick et al, 2016b] and H-line quail tend to be larger [Pick et al, 2016b, c] with higher offspring survivorship than L-line quail [Pick et al, 2016c]. Further, H-line males experience higher reproductive success than L-males, which is associated with higher testis asymmetry in H-line males [Pick et al, 2017].…”
Section: Selection Lines For Divergent Reproductive Investmentmentioning
confidence: 96%
“…when six months old; to the nearest 1g). We focused on daughters because males show a low variation in reproductive performance (Pick et al 2017).…”
Section: Breeding Conditionsmentioning
confidence: 99%
“…pleiotropic effects of loci linked to female reproductive function on IRSC). We have previously shown that female-limited selection on reproductive investment has correlated effects on male reproductive success, with males from lines selected for high female reproductive investment (H-line) siring more offspring than males from lines selected for low female reproductive investment (L-line) [ 21 ]. This pattern was observed in both a competitive mating situation (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…including male–male competition and female mate choice) and a non-competitive mating situation (i.e. excluding male–male competition and female mate choice) [ 21 ], suggesting that the male reproductive advantage was ejaculate-mediated, rather than caused by increased dominance or attractiveness [ 21 ]. We predict that if increased female reproductive investment is genetically linked to increased male-induced harm (i.e.…”
Section: Introductionmentioning
confidence: 99%